Fundamentals of Entrepreneurship (ENT300) : Mira Cake House / Isabel Kimbly Jesikel … [et al.] - Jesikel, Isabel Kimbly; Bakil, Angela; Mambang, Evelyn (2017)
Layered cake industry in Sarawak experienced high growth in financial for the past few years. This healthy trend continues until now. A very high demand for this layered cake contributed to the upward trend. All the layered cake industry segments in which Mira Cake House has witnessed a growth in demand in terms of financial since the year 2008. This cake house saw an upward trend after a severe downturn period, due to customers demand and better credit terms helped to build positive sentiments. This cake house has five branches in total in Malaysia; with four branches in Kuching and one newly open branch in Kuala Lumpur. Mira Cake House has at least 100 types of layered cake that they produced due to demands from their customers. They too already have their regular customers that come from different parts of Malaysia. This layered cakes have high demand during festive seasons such as during Hari Raya. A consistently high performer, Mira Cake House is one of the most well known business in the state of Sarawak. This cake house started from just being a small kiosk open up in a village called Kampung Boyan. They had received many positive feedbacks from their customers until they decided to expand its operation business to what it is now.